Conditional deletion of E11/Podoplanin in bone protects against ovariectomy-induced increases in osteoclast formation and activity. Issue 1 (10th January 2020) - Staines, Katherine A.; Hopkinson, Mark; Dillon, Scott; Stephen, Louise A.; Fleming, Robert; Sophocleous, Antonia; Buttle, David J.; Pitsillides, Andrew A.; Farquharson, Colin
Abstract: E11/Podoplanin (Pdpn) is implicated in early osteocytogenesis and the formation of osteocyte dendrites. This dendritic network is critical for bone modelling/remodelling, through the production of receptor activator of nuclear factor κ B (RANK)-ligand (RANKL). Despite this, the role of Pdpn in the control of bone remodelling is yet to be established in vivo . Here we utilised bone-specific Pdpn conditional knockout mice (cKO) to examine the role of Pdpn in the bone loss associated with ovariectomy (OVX). MicroCT revealed that Pdpn deletion had no significant effect on OVX-induced changes in trabecular microarchitecture. Significant differences between genotypes were observed in the trabecular pattern factor ( P <0.01) and structure model index ( P <0.01). Phalloidin staining of F-actin revealed OVX to induce alterations in osteocyte morphology in both wild-type (WT) and cKO mice. Histological analysis revealed an expected significant increase in osteoclast number in WT mice ( P <0.01, compared with sham). However, cKO mice were protected against such increases in osteoclast number. Consistent with this, serum levels of the bone resorption marker Ctx were significantly increased in WT mice following OVX ( P <0.05), but were unmodified by OVX in cKO mice. Gene expression of the bone remodelling markers Rank, Rankl, Opg and Sost were unaffected by Pdpn deletion. Together, our data suggest that an intact osteocyte dendritic network is required for sustaining osteoclast formation and activity in the oestrogen-depleted state, through mechanisms potentially independent of RANKL expression. This work will enable a greater understanding of the role of osteocytes in bone loss induced by oestrogen deprivation.